2014
DOI: 10.1002/2014rg000458
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better integration of biological data from precipitation manipulation experiments into Earth system models

Abstract: The biological responses to precipitation within the terrestrial components of Earth system models, or land surface models (LSMs), are mechanistically simple and poorly constrained, leaving projections of terrestrial ecosystem functioning and feedbacks to climate change uncertain. A number of field experiments have been conducted or are underway to test how changing precipitation will affect terrestrial ecosystems. Results from these experiments have the potential to vastly improve modeled processes. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 269 publications
(350 reference statements)
0
42
0
1
Order By: Relevance
“…Results from this experiment showed that even small increases in precipitation intensity can result in large increases in plant available soil water and subsequent plant growth [51]. More specifically, greater precipitation intensity can increase woody plant growth by driving water deeper into the soil where it is less available to grass roots [30]. Our study provides evidence that savannas respond quickly to small increases in mean precipitation intensity, but because woody plants can accumulate the effects of these short-term benefits, that occasionally intense precipitation events caused by climate change are likely to increase shrub encroachment at least until these effects interact with factors such as fire and herbivory [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from this experiment showed that even small increases in precipitation intensity can result in large increases in plant available soil water and subsequent plant growth [51]. More specifically, greater precipitation intensity can increase woody plant growth by driving water deeper into the soil where it is less available to grass roots [30]. Our study provides evidence that savannas respond quickly to small increases in mean precipitation intensity, but because woody plants can accumulate the effects of these short-term benefits, that occasionally intense precipitation events caused by climate change are likely to increase shrub encroachment at least until these effects interact with factors such as fire and herbivory [23].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this understanding of water cycling, aboveground net primary productivity has been found to increase with precipitation intensity in arid grasslands, but decrease with precipitation intensity in mesic grasslands [25]. While a handful of studies do support our understanding of precipitation intensity in North American grasslands, there remains a recognized need for experiments to test the aboveground and belowground effects of increased precipitation intensity in sites with both woody plants and grasses [2, 11, 29, 30]. Further, there is recognized need for multi-year experiments because many of the precipitation intensity experiments that have been performed to date have been limited to single growing seasons [2, 11, 29, 31].…”
Section: Introductionmentioning
confidence: 97%
“…Overall, long-term productivity responses to rainfall additions were consistent with current theory, suggesting that production may exceed values predicted from site-based temporal models after plant communities adjust to new environmental conditions. To our knowledge, temporal patterns of sensitivity and simultaneous changes in community composition have not been evaluated previously due to the lack of long-term experiments capable of linking plant community change with ecosystem sensitivity (Smith et al 2014). Based on our analyses, we conclude that (1) spatial models of sensitivity may not provide accurate predictions for climate change scenarios at the site-level, at least on decadal time scales, and (2) within an ecosystem or biome, plant community changes may actually stabilize relationships between annual precipitation and ANPP in the near term.…”
Section: Discussionmentioning
confidence: 99%
“…2010; Egea et al . 2011), indicating a need for more data describing these responses in the field (Smith et al . 2014).…”
Section: Introductionmentioning
confidence: 99%